2000
DOI: 10.1128/jcm.38.5.1782-1785.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the VITEK 2 System for Rapid Identification of Yeasts and Yeast-Like Organisms

Abstract: The new VITEK 2 system is a fully automated system dedicated to the identification and susceptibility testing of microorganisms. In conjunction with the VITEK ID-YST card the VITEK 2 system allows the identification of clinically important yeasts and yeast-like organisms in 15 h due to a sensitive fluorescence-based technology. The ID-YST card consists of 47 biochemical reactions. The database comprises 51 taxa, including newly described species. In this study we evaluated the reliability of the VITEK ID-YST c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
2
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 21 publications
(22 reference statements)
2
39
2
2
Order By: Relevance
“…The present results were better than those obtained by Graf et al [8], who reported unequivocal identification for 87.6% of isolates when using ID 32 C as the reference method. The number of misidentifications (1.7%) was comparable with the results in the present study, but the number of low discriminations was greater.…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…The present results were better than those obtained by Graf et al [8], who reported unequivocal identification for 87.6% of isolates when using ID 32 C as the reference method. The number of misidentifications (1.7%) was comparable with the results in the present study, but the number of low discriminations was greater.…”
contrasting
confidence: 97%
“…This could have been caused partly by the selection of strains, but the improved performance in the present study may also be a result of the development of the Vitek 2 database. Identification of C. guilliermondii and Candida lusitaniae was problematic, both in the study by Graf et al [8] and in the present study, whereas all C. glabrata isolates were identified without difficulty. This is in contrast to the study by Massonet et al [9], in which most difficulties were encountered with C. glabrata.…”
contrasting
confidence: 65%
“…The Vitek 2 ID-YST is a fully automated system, with a database that comprises C. dubliniensis. The profit of correct identification is similar to that of other commercial systems and may be increased if morphological characteristics are evaluated (Graf et al, 2000). According to Gales et al (1999), clinical laboratories could use the absence of growth at 45°C and a negative D-xylose test with either the API 20C AUX or Vitek system to provide a presumptive identification of C. dubliniensis.…”
Section: Agar Methodsmentioning
confidence: 98%
“…The isolation of Candida and the identification of the species were obtained by cultures on chromogenic agar (CHROMagar Candida, Vacutest Kima, Padova, Italy) 10 ; when CHROMagar did not allow certain identification of the species, an automated yeast biochemical identification system was used (Vitek card, BioMérieux, Marcy-lÕEtoile, France). 11 Women who entered the study were treated with fluconazole 150 mg weekly for 6 months. In addition, a sealed anonymous envelope containing either three pairs of white Dermasilk briefs or three pairs of white cotton briefs, was given to each patient.…”
Section: Methodsmentioning
confidence: 99%